Slove this question with explainton
Wrong Answer ❌❌ = Report
Correct Answer ✅✅ = brainlist and thanks
Attachments:
![](https://hi-static.z-dn.net/files/d3d/a143ce76d91dad7010b5a1b428a0a321.jpg)
Anonymous:
kar diye yahan tak
Answers
Answered by
26
Answer:
(a) 9pq
= 9 (-4) (1)
= -36
(b)
= 16 - 1
= 15
(c)
(d)
Answered by
2
9pq (if p = -4 and q = 1)
9 (-4)(1) = -36
p² - q² (if p = -4 and q = 1)
(-4)² - (1)² = (-4 +1) (-4 -1) = -3 × -5 = 15
《Identity Used : a² - b² = (a+b)(a-b)》
2p² + 7pq + q² (if p = -4 and q = 1)
2(-4)(-4) + 7(-4)(1) + (1)²
= 32 - 28 + 1 = 5
(if p = -4 and q = 1)
=
=
Similar questions